Magma Dynamics with the Enthalpy Method: Benchmark Solutions and Magmatic Focusing at Mid-ocean Ridges - Katz, R (2008)
Magma genesis and transport link mantle convection with surface volcanism and hence with the long-term chemical and morphological evolution of the Earth's crust. Modeling the dynamics of magma-mantle interaction in tectonic settings remains a challenge, however, because of the complexity of multi-component thermodynamics and melt segregation in a permeable, compactible, and actively deforming mantle matrix. Here I describe a flexible approach to formulating the thermochemistry of such models based on the Enthalpy Method, a technique commonly used in simulations of alloy solidification. This approach allows for melting and freezing based on a familiar binary phase diagram, consistent with conservation of energy and two-phase compaction and flow. I present an extension of the Enthalpy Method to more than two thermodynamic components. Simulation of a one-dimensional upwelling and melting column provides a benchmark for the method. Two-dimensional simulations of the melting region that feeds magma to a rapidly spreading mid-ocean ridge demonstrate the utility of the Enthalpy Method. These calculations provide a new estimate of the efficiency of magmatic focusing along the base of the oceanic lithosphere. Modeled focusing efficiency varies with mantle permeability and resistance to compaction. To yield 5-7 km of oceanic crust with ∼20% melting of a homogeneous, sub-ridge mantle, a focusing efficiency of greater than 70% is required. This, in turn, suggests that matrix permeability and bulk viscosity are at the high end of previously estimated values. © The Author 2008. Published by Oxford University Press. All rights reserved.